Χειρόγραφη επιστολή προς το Υπουργείο Γεωργίας Αθηνών για την υποβολή αντίγραφου της υπ΄αριθ.349 αναφοράς.
Χειρόγραφη επιστολή προς το Υπουργείο Γεωργίας Αθηνών για την υποβολή αντίγραφου της υπ΄αριθ.349 αναφοράς.